2003
DOI: 10.1016/s0014-5793(03)00117-0
|View full text |Cite
|
Sign up to set email alerts
|

A cadherin‐like protein functions as a receptor for Bacillus thuringiensis Cry1Aa and Cry1Ac toxins on midgut epithelial cells of Bombyx mori larvae

Abstract: Aminopeptidase N (APN) and cadherin-like protein (BtR175) from Bombyx mori larvae were examined for their roles in Cry1Aa-and Cry1Ac-induced lysis of B. mori midgut epithelial cells (MECs). APNs and BtR175 were present in all areas of the midgut, were particularly abundant in the posterior region, and were found only on columnar cell microvilli and not on the lateral membrane that makes cell^cell contacts. This distribution was in accordance with the distribution of Cry1A-susceptible MECs in the midgut. The ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 48 publications
5
56
0
Order By: Relevance
“…1B and Movie 1). Cell swelling and lysis occurred within a short time frame (30-40 min after toxin exposure), a phenomenon also observed in other insect cells (9,40) as well as in mammalian cells transfected with the cDNA of BT-R receptors (11). The morphological changes observed in Cry1Ab toxin-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…1B and Movie 1). Cell swelling and lysis occurred within a short time frame (30-40 min after toxin exposure), a phenomenon also observed in other insect cells (9,40) as well as in mammalian cells transfected with the cDNA of BT-R receptors (11). The morphological changes observed in Cry1Ab toxin-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The specificity of Cry toxins depends on individual cell surface receptors, which represent a family of cadherins expressed in the midgut epithelium of various insects (9)(10)(11)(12)(13). Cytotoxicity and cell death are the direct result of univalent binding of a Cry toxin monomer to its respective cadherin receptor (14).…”
mentioning
confidence: 99%
“…Nagamatsu et al (129) showed that exposure to 8 g/ml Cry1Aa caused BtR175-expressing Sf9 cells, but not control cells, to swell within 15 min, and the number of swollen cells increased for 45 min after the addition of the toxin. These changes were quite similar to those of midgut columnar cells in B. mori fed with Cry1Aa and to those of epithelial cells isolated from the midgut and treated with toxin ex vivo (66). In another study, Cry1Aa caused cell swelling and cytotoxicity in mammalian cells expressing BtR175b (an allelic variant of BtR175) (171).…”
Section: Btr175 (Bombyx Mori)mentioning
confidence: 59%
“…In contrast, an analysis of the cytoplasmic domain did not reveal sequences known to interact with intracellular proteins such as catenins (33). While classical cadherins are located primarily within adherens junctions involved in cell-cell adhesion (4), lepidopteran cadherin-like proteins have been identified on the apical membrane of midgut columnar epithelial cells (3,24,66,124), the target site of Cry toxins (16,19,20,24). The expression of cadherin has been shown to vary with developmental stage and increases progressively from the first to the fifth instar in M. sexta larvae (124).…”
Section: Cadherinmentioning
confidence: 99%
“…Recently, Gahan et al (2001) discovered a Cry1Ac-resistant Heliothis virescens strain carrying a mutated CadLP gene. Hara et al (2003) demonstrated that an antibody to CadLP (BtR175) inhibits the Cry1A toxin-mediated release of lactate dehydrogenase from midgut cells, thereby supporting the idea that CadLP may be a receptor for Cry1A toxins. Similarly, Gomez et al (2001) reported that a phage display-derived peptide inhibits the specific binding between CadLP and Cry1Ab, whereas it did not disrupt the binding between aminopeptidase N (APN) and Cry1Ab.…”
Section: Introductionmentioning
confidence: 75%